Being a clinical nurse in times of pandemic: When the groundbreaking system is urgently needed - Septiani, Diah; Ba, May Sein (Universitas Muhammadiyah Magelang, 2021)
COVID-19 impacted the life and health of people worldwide including the healthcare team in Hospitals. As a consequence, this situation disturbs the healthcare systems along with the care provider such as nurses fighting as the frontlines to save the patient’s lives. Exploring the issues during their work time will support them and lead an innovative strategy on how to improve the outcome and reduce the morbidity among nurses. This paper explored the nurses’ experience when taking care of patients with COVID-19 infection in the Intensive Care Unit of Mental Health Hospital “Prof. Soerojo” Magelang, City. It is hoped that this article will encourage the nurses to keep helping the patient, endlessly.